Learning to Recognize Unfamiliar Voices: An Online Study With 12- and 24-Month-Olds - Orena, Adriel John; Mader, Asia Sotera; Werker, Janet F. (Frontiers in Psychology, 2022)
Young infants are attuned to the indexical properties of speech: they can recognize highly familiar voices and distinguish them from unfamiliar voices. Less is known about how and when infants start to recognize unfamiliar voices, and to map them to faces. This skill is particularly challenging when portions of the speaker’s face are occluded, as is the case with masking. Here, we examined voice-face recognition abilities in infants 12- and 24-months of age. Using the online Lookit platform, children saw and heard four different speakers produce words with sonorous phonemes (high talker information), and words with phonemes that are less sonorous (low talker information). Infants aged 24-months, but not 12-months, were able to learn to link the voices to partially occluded faces of unfamiliar speakers, and only when the words were produced with high talker information. These results reveal that 24-month-old infants can encode and retrieve indexical properties of an unfamiliar speaker’s voice, and they can access this information even when visual access to the speaker’s mouth is blocked.